Effect of gold layer thickness on the low-temperature crystallization process of germanium thin films by gold-induced crystallization. (5th August 2020) - Sunthornpan, Narin; Tauchi, Kohtaroh; Tezuka, Nairu; Kyuno, Kentaro
Abstract: The effect of Au layer thickness (1, 2.5, 5, 7.5 and 10 nm) on the low-temperature crystallization of Ge thin films (30 nm) was examined. It is found that the best Ge crystallinity is achieved at an Au layer thickness of 2.5 nm. This finding will open up the possibility to reduce the amount of Au consumption in the low-temperature crystallization process of Ge thin films.